The future of education: “Freedom” as the foundation of the curriculum - Nadira Salsabila; Akmalia Faldia Ihtisani; Izza Zahrotul Mufidah (Universitas Pendidikan Indonesia, 2024)
The Merdeka Curriculum is characterized by an innovative approach in the educational context that provides teachers and students with greater freedom to develop and manage learning processes that aim to increase students' creativity, initiative, and responsibility in facing dynamic changes in science. This article encourages further discussion and a deeper understanding of the curriculum to create a more effective and appropriate learning environment for students. This article also discusses the concept of freedom of learning and its relationship to thinking and innovation. The research method used is a literature study to collect and analyze information from previous studies. The findings and discussion relate to the determination of the 2020 independent curriculum, its differences from the previous curriculum, and its impact on teaching staff and students. One important outcome of the self-paced curriculum is the emphasis on developing cultural agility as an important skill for future professionals.